Somatoform dissociation, fatigue severity and pain behavior compared in patients with migraine headache and in healthy individuals - Ghasem Fattahzadeh-Ardalani; Vida Aghazadeh; Abolfazl Atalu; Vahid Abbasi (MDPI AG, 2017)
The prevalence of migraine in the world is about 15 and 7% among women and men, respectively. The purpose of this study was comparison of somatoform dissociation, fatigue severity and pain behavior in patients with migraine headache and its relationship with coping strategies. This descriptive analytical study has been done on 120 patients with migraine headache and 120 healthy subjects were selected randomly. Data collected by somatoform dissociation questionnaire (SDQ-20), fatigue severity scale, pain behavior scale and coping strategies scale. For data analysis we used SPSS.19. The means of the somatoform dissociation, pain behavior scale, help searching subscale and pain compliant in migraine and healthy subjects were statistically significant. There was not significant difference in avoidance subscales between the two groups. Comparison of fatigue severity in patients with migraine and control group was meaningful. There was significant positive correlation between all four scales and coping strategies. It seems that these symptoms can play an important role in this disease; thus, their careful evaluation in the treatment of migraine headache is essential.